2016
DOI: 10.1002/ejic.201600744
|View full text |Cite
|
Sign up to set email alerts
|

Tetranuclear Lanthanide(III) Complexes Containing a Square‐Grid Core: Synthesis, Structure, and Magnetism

Abstract: The reactions of Ln(NO3)3·5H2O (Ln = Dy3+, Tb3+, Ho3+, Er3+) and a multidentate flexible ligand, (E)‐N′‐[2‐hydroxy‐3‐(hydroxymethyl)‐5‐methylbenzylidene]‐6‐(hydroxymethyl)picolinohydrazide (LH4), in the presence of Et3N in a 1:1:3 molar ratio afforded a series of complexes [Ln4(LH2)4(µ2‐OH)4]·xCH3OH·yH2O (Dy3+, x = 2, y = 2; Tb3+, x = 4, y = 5; Ho3+, x = 0, y = 13; Er3+, x = 4, y = 6). X‐ray diffraction analysis revealed that all the complexes are neutral and possess a distorted [2 × 2] square‐grid core [Ln4(µ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 122 publications
0
9
0
Order By: Relevance
“…The multisite coordinating Schiff base ligand LH 3 was synthesized by condensation reaction in methanol of 2‐(hydroxymethyl)‐6‐carbaldehyde‐4‐methylphenol, with 2‐aminophenol. Recently, we and others, have utilized the above‐mentioned aldehyde or corresponding multi‐compartmental Schiff base ligands to ensemble various 3d‐4f heterometallic complexes . The aldehyde [2‐(hydroxymethyl)‐6‐carbaldehyde‐4‐methylphenol] used here for Schiff base preparation is synthetically modified o ‐vanillin where terminal weakly coordinating methoxy (–OMe) group of o ‐vanillin has been substituted by alkoxy (–CH 2 OH) group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The multisite coordinating Schiff base ligand LH 3 was synthesized by condensation reaction in methanol of 2‐(hydroxymethyl)‐6‐carbaldehyde‐4‐methylphenol, with 2‐aminophenol. Recently, we and others, have utilized the above‐mentioned aldehyde or corresponding multi‐compartmental Schiff base ligands to ensemble various 3d‐4f heterometallic complexes . The aldehyde [2‐(hydroxymethyl)‐6‐carbaldehyde‐4‐methylphenol] used here for Schiff base preparation is synthetically modified o ‐vanillin where terminal weakly coordinating methoxy (–OMe) group of o ‐vanillin has been substituted by alkoxy (–CH 2 OH) group.…”
Section: Resultsmentioning
confidence: 99%
“…The aldehyde [2‐(hydroxymethyl)‐6‐carbaldehyde‐4‐methylphenol] used here for Schiff base preparation is synthetically modified o ‐vanillin where terminal weakly coordinating methoxy (–OMe) group of o ‐vanillin has been substituted by alkoxy (–CH 2 OH) group. Now, depending upon the deprotonation level, the alkoxy group can show bridging coordination action to enable the expansion of the metal cluster . The semi‐flexible Schiff base possess total of four donor sites: two phenolic oxygen, one benzyl alcoholic oxygen and one imino nitrogen.…”
Section: Resultsmentioning
confidence: 99%
“…In 2016 Biswas et al designed and synthesized one multidentate flexible ligand L6 which upon reaction with Ln(NO 3 ) 3 ·5H 2 O formed tetranuclear [2 × 2] homometallic grid complexes, [Ln III 4 ( L6 2 ) 4 (μ 2 -OH) 4 ]· x CH 3 OH· y H 2 O (Ln = Dy, Tb, Ho, Er), with lanthanide metals. 51 Reported ligand L6 contained two ONO coordination pockets and was able to bind with two Ln III ions. Lanthanide complexes of ligands composed of four Ln III ions were held together by two coordination pockets of perpendicular dianionic ligands [LH 2 ] 2− .…”
Section: Pyridine-based Ligandsmentioning
confidence: 99%
“…Zhang and co-workers have reported the first genuine 3d-4f cocrystal of a mononuclear Dy III complex with a square-planar Cu II complex consisting of only one reactant . In fact, the field of lanthanide coordination chemistry has gained a lot of attention because of its potential applications in catalysts, photoluminescent materials, and molecular magnetic materials. Compounds containing lanthanide (Ln) ions are of special interest in the field of molecular magnetism because they may exhibit an extraordinary slow relaxation of magnetization behavior or single molecule/ion magnet (SMM/SIM) behavior arising from the large spin and significant magnetic anisotropy of Ln III ions. Despite substantial progress in the field of SMMs, it is worth mentioning that QTM-induced relaxation processes are the biggest roadblock in lowering the effective energy barrier ( U eff ) of lanthanide-containing SMM complexes. , There are a few strategies to mitigate the QTM, such as ligand fields of high symmetries around the lanthanide ions, application of a tiny static magnetic field, dilution of such complexes in a diamagnetic matrix, or a strong superinteraction among the paramagnetic ions (3d and 4f metal ions). , However, a review of the literature has shown that magnetic exchange coupling resulting from 3d/4f metal ions is often weak and has a small effective energy barrier, but when paramagnetic 3d ions are replaced by diamagnetic metal ions, it may offer magnetic dilution to the system, slowing the QTM process and elevating the energy barrier. , Furthermore, recent studies revealed that the presence of diamagnetic coordinating ions in a Dy III system can alter the electron density distribution around the Dy III ion (particularly around the bridging phenoxido oxygen donor), influencing the orientation of the Dy III g tensor and therefore increasing the energy barrier. …”
Section: Introductionmentioning
confidence: 99%